2022
DOI: 10.3389/fpubh.2022.940898
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of malaria and anemia in high and low malaria-endemic North-Eastern districts of India

Abstract: Anemia and malaria are the two major public health problems that lead to substantial morbidity and mortality. Malaria infection destroys erythrocytes, resulting in low hemoglobin (Hb) levels known as anemia. Here we report the determinants of anemia in high and low malaria-endemic areas that would help understand which parasite densities, age, and gender-associated low Hb levels. Therefore, a cross-sectional mass survey (n = 8,233) was conducted to screen anemia and malaria in high and low malaria-endemic dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…52 The odds of being anemic among female malaria-infected patients were 3.2 times higher than those of their male counterparts. This finding was supported by a study done in India, 53 and Cameroon. 54 The possible explanation might be due to chronic blood loss and abnormal menstrual function among female participants.…”
Section: Dovepresssupporting
confidence: 76%
“…52 The odds of being anemic among female malaria-infected patients were 3.2 times higher than those of their male counterparts. This finding was supported by a study done in India, 53 and Cameroon. 54 The possible explanation might be due to chronic blood loss and abnormal menstrual function among female participants.…”
Section: Dovepresssupporting
confidence: 76%
“…This process lowers the amount of red blood cells and can in a severe stage cause severe anemia. 9 - 12 …”
Section: Discussionmentioning
confidence: 99%
“…Cross-border malaria along with poor surveillance and high climatic suitability are major drivers of malaria transmission in these states 31. Recent studies have been unable to find a clear association between malnutrition and malaria in high malaria-endemic districts in the northeast 32…”
Section: Discussionmentioning
confidence: 99%
“…31 Recent studies have been unable to find a clear association between malnutrition and malaria in high malaria-endemic districts in the northeast. 32 The endemic states exhibited considerable districtwise heterogeneity in their malaria caseload/API. We observed that underweight children form high-high clusters and these clusters were spread uniformly in the eastern, central and western states of India, and overlapped with highly malaria-endemic districts (API >1)-Chhattisgarh, Jharkhand, Madhya Pradesh, Maharashtra and Odisha.…”
Section: Bmj Global Healthmentioning
confidence: 99%